Processing and Value-addition of Maize for Food and Nutrition Security - Singh, Usha (Indian Farming, 2015)
A number of nutritional products from QPM such as weaning food, health food, specialty foods has been developed by the Rajendra Agricultural University in collaboration with the Directorate of Maize Research. The commercialization of agro based food products is the output of FEIP (Farmer, Entrepreneur, Institution and People) chain, a revolutionary concept which under strategic planning will definitely be able to strengthen value chain in maize for food and nutritional security and ultimately livelihood security.